2010
DOI: 10.3109/10520295.2010.492733
|View full text |Cite
|
Sign up to set email alerts
|

An innovative brilliant blue FCF method for fluorescent staining of fungi and bacteria

Abstract: Most natural and synthetic dyes currently used for microbial fluorescent staining are toxic or carcinogenic and are harmful to animals, humans and the environment. A food dye for microbial staining, brilliant blue FCF, was used as an alternative to lactofuchsin and lactophenol blue. Brilliant blue FCF shows pronounced microbial cell fluorescence staining of an array of pathogenic/toxigenic (Fusarium granunearum 3- and 15-acetyldeoxynivalenol chemotypes, and Escherichia coli O157:H7) and beneficial fungi and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Using this method, tissue samples can be rapidly analyzed by histological analyses, such as immunohistochemistry and FISH, in order to screen genetic or protein markers, or to detect tissues infected with pathogenic/toxigenic factors. Since most dyes currently used for microbial fluorescent staining are toxic or carcinogenic, a tissue array system using brilliant blue FCF, which is a food dye and thus has no toxic effects, was developed and applied for microbial cell fluorescence staining of pathogenic/toxigenic and beneficial fungi and bacteria [ 107 ].…”
Section: Application Of Fluorescence-based Bioassaysmentioning
confidence: 99%
“…Using this method, tissue samples can be rapidly analyzed by histological analyses, such as immunohistochemistry and FISH, in order to screen genetic or protein markers, or to detect tissues infected with pathogenic/toxigenic factors. Since most dyes currently used for microbial fluorescent staining are toxic or carcinogenic, a tissue array system using brilliant blue FCF, which is a food dye and thus has no toxic effects, was developed and applied for microbial cell fluorescence staining of pathogenic/toxigenic and beneficial fungi and bacteria [ 107 ].…”
Section: Application Of Fluorescence-based Bioassaysmentioning
confidence: 99%
“…enterocolitica, and Legionella pneumophila, with the lowest detection limit being 10 2 CFU/mL . In another study, Chau et al (2011) used RuBpy: [Ru­(bpy)­3]­Cl2/Tris­(bipyridine) ruthenium­(II) chloride as a signal for sandwich fluorescent immunoassay to detect Staphylococcal enterotoxin B . Han et al (2013) employed an ELISA-based array using FluoSpheres to detect Staphylococcal enterotoxin B .…”
Section: Introductionmentioning
confidence: 99%
“… 26 In another study, Chau et al (2011) used RuBpy: [Ru(bpy)3]Cl2/Tris(bipyridine) ruthenium(II) chloride as a signal for sandwich fluorescent immunoassay to detect Staphylococcal enterotoxin B. 27 Han et al (2013) employed an ELISA-based array using FluoSpheres to detect Staphylococcal enterotoxin B. 28 These examples illustrate the versatility and widespread use of fluorescent labeling in microarray technology, which greatly aids in analyzing various biomolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Brilliant blue FCF is a water-soluble triphenylmethane dye, generally used as a water tracer agent . Due to its nontoxic activities, brilliant blue has been used as a food colorant as well as to stain cell bacterial and fungal cells. , Weber et al reported that brilliant blue shows an allergic reaction in some bronchial asthma patients . The photocytotoxicity of triphenylmethane dye depends on the production of reactive oxygen species with regard to their photodynamic therapy .…”
Section: Introductionmentioning
confidence: 99%